The Effect of Holding Time in Cyclic Heat Treatment Process on Network Carbide Structure of Carburized Carbon Steel - Thammachot, Narongsak; Homjabok , Wanna; Mayai, Amornsak; Noyming, Sombut (Recent Science and Technology, 2020)
The objective of this research was to study the effect of holding time of cyclic heat treatment on network carbide and mechanical properties of pack carburized low carbon steel. The experiments were conducted by heating the specimens over critical temperature A1 line at 780 °C followed by cooling down to lower critical temperature A1 line at temperature of 680°C. The cycles of heating and cooling were 5 cycles, each of cycle was held at 0, 5 and 10 minutes. They were then hardened by austenitizing temperature of 780 °C with the holding time of 30 minutes followed by quenching in water. Finally, the specimens were tempered at 180 °C for 30 minutes. The microstructure inspection and mechanical properties testing were carried out. The results of this experiment showed that the microstructure of pack carburized specimens consisted of pro-eutectiod cementite or network carbide in pearlite matrix. After cyclic heat treatment, the pro-eutectiod cementite and eutectoid cementite structure transformed to spheroidized carbides and distributed in pearlite matrix. The tendency of spheroidized carbides grew when the holding time increased. After hardening and tempering, the pearlite matrix transformed to martensite matrix with the distributed of spheroidized carbides. The mechanical properties such as hardness, impact and tensile strength tended to rise when the holding time increased.